Analisis Kinerja Operasional Dermaga Pelabuhan Jangkar Situbondo (Ditinjau berdasarkan nilai Berth Occupancy Ratio selama 6 bulan) - Syifa Aulia; Nurul Amalia Silviyanti Siswoyo; Bodi Gunawan (Program Studi Teknik Kelautan Universitas Abdurachman Saleh Situbondo, 2023)
Ports play an important role for a region. As an entry gate that connects regions, ports have a role in revitalizing the economy and regional development. Situbondo Regency has a main port, namely Jangkar Port. Located in Jangkar District, Situbondo Regency, this port connects the island of Java-Madura-Lombok. Having a strategic location and a large number of interested parties makes Jangkar Port worthy of consideration for development. Therefore,it is necessary to carry out an analysis of the dock as consideration for the future development of Jangkar Port. The analysis carried out by calculating the Berth Occupancy Ratio (BOR) value, namely calculating the comparison of the time for using the dock with the time available in the time period expressed as a percentage. Based on research, the results obtained were 15,1 % and showed that the use of docks at Jangkar Port still met standards because it did not exceed the 40% limit in accordance with UNCTAS provisions for dock with one berth.